Lithium-rich lithium ferrite lithium supplement agent as well as synthesis method and application thereof

By forming a mixed cladding layer composed of solid electrolyte, conductive carbon and elemental sulfur on the surface of lithium-rich lithium ferrate, the shortcomings of existing lithium supplement agents in air stability, conductivity and safety are solved, and a more efficient and reliable lithium supplement effect is achieved.

CN119905695AActive Publication Date: 2025-04-29TIANJIN GUOAN MGL NEW MATERIALS TECH CO LTD

Patent Information

Application Number
CN202510405885.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-04-29
Estimated Expiration
2045-04-02

AI Technical Summary

Technical Problem

The existing lithium-rich lithium ferrate supplements have shortcomings in air stability, conductivity and safety, which affects their application in lithium-ion batteries.

Method used

By mixing the solid electrolyte, conductive carbon and elemental sulfur for low temperature heat treatment, a composite mixture is formed, and secondary mixing and low temperature heat treatment are carried out with lithium-rich lithium ferrate to form a mixed coating layer to improve the air stability and conductivity of the lithium supplement agent.

Benefits of technology

It effectively improves the air stability and conductivity of lithium-rich lithium ferrate supplement agent, reduces gas production during charging, and improves lithium-added capacity and battery safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905695A_ABST
    Figure CN119905695A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and provides a lithium-rich lithium ferrite lithium supplement agent and a synthesis method and application thereof.The synthesis method comprises the steps that solid electrolyte, conductive carbon and elemental sulfur are mixed and subjected to low-temperature heat treatment to form a composite mixture, then the composite mixture and lithium-rich lithium ferrite are subjected to secondary mixing and low-temperature heat treatment, and the lithium-rich lithium ferrite lithium supplement agent is obtained. And enabling the composite mixture to form a mixed coating layer to obtain the lithium-rich lithium ferrite lithium supplement agent. Sulfur in the mixed coating layer can absorb surface released oxygen in the charging process of the lithium-rich lithium ferrite, so that gas production is reduced, the solid electrolyte and conductive carbon can form an ion and electron conductive network, and the problems that Li < + > is difficult to separate and the lithium supplementing capacity is reduced due to too thick sulfur coating are avoided. Meanwhile, the elemental sulfur is melted through low-temperature heat treatment, so that the dispersing and bonding effects can be achieved, uniform dispersion of the solid electrolyte and the conductive carbon and effective coating of the composite mixture are achieved, the binding property and compatibility can be improved, and the air stability of the lithium supplementing agent can be effectively improved through the obtained mixed coating layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials and relates to a lithium-rich lithium ferrate lithium supplement agent and a synthesis method and application thereof. Background Art

[0002] Lithium-ion batteries have been widely used in portable electronic products and new energy vehicles due to their high voltage, high energy density, long cycle life and environmental friendliness. With the rapid expansion of the electronic equipment and electric vehicle markets, the requirements for lithium-ion battery performance are also increasing. However, existing lithium-ion batteries have the problem of irreversible capacity loss during the first charge and discharge process, which not only affects the energy density of the battery, but also limits its cycle performance, shortens its service life, and affects the actual application effect.

[0003] The problem of irreversible capacity loss mainly stems from the fact that during the first charge of a lithium-ion battery, the electrolyte undergoes a reduction reaction on the negative electrode surface to form a solid electrolyte interface (SEI). The formation of the SEI film consumes some lithium ions, resulting in irreversible capacity loss; at the same time, some active substances may undergo irreversible structural changes or decomposition during the first charge and discharge process, further increasing the irreversible capacity loss. In order to solve this problem, lithium supplementation technology came into being.

[0004] The core of lithium replenishment technology is to improve the initial capacity and overall performance of the battery by adding additional lithium sources. It mainly includes two ways, namely, negative electrode lithium replenishment by pre-depositing lithium metal or lithium alloy on the surface of the negative electrode material, and positive electrode lithium replenishment by adding lithium replenishment additives to the positive electrode material. Among them, the positive electrode lithium replenisher can release lithium ions during the first charging of the battery, and then compensate for the lithium ion loss during the formation of the negative electrode SEI film. Relatively speaking, the use of positive electrode lithium replenishers is relatively more stable and safe, and the process is simple and has a wider applicability.

[0005] Common positive electrode lithium supplements include lithium-rich lithium iron oxide ( )、Lithium-rich lithium manganese oxide( ) and so on. Among them, lithium-rich lithium iron oxide has attracted much attention due to its high irreversible lithium replenishment capacity (≥700mAh / g) and low cost advantages. However, lithium-rich lithium iron oxide has poor air stability, which can easily lead to structural damage and performance degradation of the material. Secondly, the electronic conductivity of lithium-rich lithium iron oxide is low, which limits its fast charging and discharging performance in the battery. In addition, lithium-rich lithium iron oxide is prone to produce gas during the battery cycle, affecting the safety and stability of the battery.

[0006] In response to the above-mentioned problems of lithium-rich iron oxide, researchers proposed to coat the surface of lithium-rich iron oxide with a protective layer of oxides such as Al2O3 and SiO3 to prevent contact with air and maintain structural stability. However, this coating will affect the transmission path of lithium ions, further reducing the conductivity and electrochemical properties of the material. In order to improve electronic conductivity, researchers introduced highly conductive carbon materials, such as carbon nanotubes and graphene, to composite with lithium-rich iron oxide. However, the distribution uniformity of conductive carbon materials and compatibility with matrix materials need to be further resolved. At the same time, the traditional process for synthesizing lithium-rich iron oxide requires sintering through solid-phase mixing, and then coating or doping with conductive carbon materials through high-temperature sintering. However, high-temperature treatment can easily induce carbon thermal reduction reaction, causing Fe 3+ Reduced to Fe 2+ , resulting in problems of phase impurity and capacity attenuation.

[0007] Therefore, there is still a need to develop and optimize lithium-rich lithium iron oxide lithium supplement additives to solve the existing problems and provide more efficient and reliable solutions to further promote its large-scale lithium supplement application. Summary of the invention

[0008] In view of the problems existing in the prior art, the purpose of the present invention is to provide a lithium-rich ferrite lithium supplement and its synthesis method and use. The synthesis method comprises mixing a solid electrolyte, conductive carbon and elemental sulfur, performing low-temperature heat treatment to form a composite mixture, and then performing secondary mixing and low-temperature heat treatment with lithium-rich ferrite to form a mixed coating layer to obtain a lithium-rich ferrite lithium supplement. The present invention absorbs the surface oxygen released during the charging process of lithium-rich ferrite by adding sulfur to the mixed coating layer, thereby reducing gas production; by adding solid electrolyte and conductive carbon, a conductive network of ions and electrons is formed in the sulfur-based mixed coating layer to avoid the Li+ caused by excessively thick sulfur coating. + At the same time, the elemental sulfur melted in the two low-temperature heat treatments can play a role in dispersion and bonding, achieving uniform dispersion of solid electrolyte and conductive carbon and effective coating of the composite mixture, and is conducive to improving the binding and compatibility. The mixed coating layer obtained by the mutual coordination of the three components can effectively improve the air stability of the lithium supplement.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement, the method comprising:

[0011] A solid electrolyte, conductive carbon and elemental sulfur are mixed and subjected to a low-temperature heat treatment. The temperature of the low-temperature heat treatment causes the elemental sulfur to melt, so as to bond the solid electrolyte and the conductive carbon to form a composite mixture based on elemental sulfur. The composite mixture is then mixed with lithium-rich lithium ferrite for a second time and subjected to a second low-temperature heat treatment, so that the composite mixture forms a mixed coating layer on the surface of the lithium-rich lithium ferrite, thereby obtaining a lithium-rich lithium ferrite lithium supplement.

[0012] In order to solve the application problem of lithium-rich iron phosphate, the synthesis method of the present invention forms a mixed coating layer by coating based on elemental sulfur, wherein the sulfur can absorb surface oxygen release during the charging and discharging process of lithium-rich iron phosphate to form Li2SO3, effectively inhibiting gas production; but considering that only sulfur coating will hinder the lithium ion conduction of the lithium-rich iron phosphate in the inner core, and in order to further improve the conductivity of lithium-rich iron phosphate, the synthesis method uses a solid electrolyte and conductive carbon and sulfur to mix to form a mixed coating layer, effectively improving ionic conductivity and electronic conductivity, and can avoid the adverse effects of sulfur coating or sulfur usage. At the same time, the synthesis method uses the characteristics of low melting point of sulfur, and the two low-temperature heat treatments can convert elemental sulfur into a molten state, thereby improving the uniformity of dispersion of solid electrolyte and conductive carbon, improving the bonding and compatibility between the components, making the bonding between any two components or between the internal lithium-rich iron phosphate closer, which is conducive to the subsequent formation of a more compact mixed coating layer, and can effectively ensure that the composite mixture forms a tightly bonded mixed coating layer on the surface of lithium-rich iron phosphate. Since elemental sulfur is also hydrophobic, the mixed coating layer with the three components can further effectively improve the overall air stability of the lithium supplement.

[0013] The following are preferred technical solutions of the present invention, but are not limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0014] As a preferred technical solution of the present invention, the method for preparing the lithium-rich lithium iron oxide comprises: mixing a lithium source and an iron source in a solid phase, and then pre-sintering and sintering in sequence to obtain the lithium-rich lithium iron oxide.

[0015] As a preferred technical solution of the present invention, the lithium source includes at least one of lithium hydroxide monohydrate, anhydrous lithium hydroxide, lithium oxide, lithium carbonate or lithium nitrate. For example, typical but non-limiting combination examples include a combination of lithium hydroxide monohydrate and anhydrous lithium hydroxide, a combination of lithium hydroxide monohydrate and lithium oxide, a combination of lithium hydroxide monohydrate and lithium carbonate, a combination of lithium hydroxide monohydrate and lithium nitrate, a combination of lithium oxide and lithium carbonate, or a combination of lithium nitrate and lithium carbonate, etc.

[0016] Preferably, the iron source comprises nano-iron oxide.

[0017] Preferably, the particle size D of the nano iron oxide is 50 It is 0.02~1μm, for example, 0.02μm, 0.05μm, 0.08μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm or 1μm, etc.

[0018] Preferably, the amounts of the lithium source and the iron source are controlled according to a molar ratio of the lithium element in the lithium source to the iron element in the iron source of (5-5.6):1, for example, 5:1, 5.1:1, 5.2:1, 5.3:1, 5.4:1, 5.5:1 or 5.6:1, etc., but are not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0019] As a preferred technical solution of the present invention, the method for preparing the lithium-rich lithium ferrite also includes solid-phase mixing the additive with the lithium source and the iron source to dope the obtained lithium-rich lithium ferrite.

[0020] The present invention preferably forms Li site defects by metal cation doping to anchor lattice oxygen, thereby further improving air stability and ionic conductivity.

[0021] Preferably, the additive includes at least one of zirconium oxide, aluminum oxide, tungsten oxide, titanium oxide or magnesium oxide. For example, typical but non-limiting combination examples include a combination of zirconium oxide and aluminum oxide, a combination of zirconium oxide and tungsten oxide, a combination of aluminum oxide and titanium oxide, a combination of aluminum oxide and magnesium oxide, a combination of tungsten oxide and titanium oxide, etc.

[0022] Preferably, the amount of the additive is 0.1% to 1.2% of the mass of the lithium-rich lithium ferrite theoretically generated by the lithium source and the iron source, for example, 0.1%, 0.3%, 0.5%, 0.8%, 0.9%, 1%, 1.1% or 1.2%, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0023] As a preferred technical solution of the present invention, the pre-calcination temperature is 400-550°C, for example, 400°C, 430°C, 440°C, 450°C, 480°C, 500°C, 520°C or 550°C, and the pre-calcination time is 5-40h, for example, 5h, 8h, 10h, 12h, 15h, 18h, 20h, 23h, 25h, 28h, 30h, 33h, 35h, 38h or 40h, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0024] As a preferred technical solution of the present invention, the sintering temperature is 700-850°C, for example, 700°C, 720°C, 750°C, 780°C, 800°C, 830°C or 850°C, and the sintering time is 5-15h, for example, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h or 15h, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0025] As a preferred technical solution of the present invention, the amount of the solid electrolyte is a, and a accounts for 0.3% to 2% of the mass of the lithium-rich lithium ferrite, for example, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, etc., preferably 0.3% to 1.4%, and further preferably 0.5% to 1%, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0026] Preferably, the amount of the conductive carbon is b, and b accounts for 1% to 2.5% of the mass of the lithium-rich lithium ferrite, for example, 1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.%, 2.2%, 2.3%, 2.4% or 2.5%, etc., preferably 1.2% to 2.1%, and further preferably 1.3% to 1.7%, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0027] Preferably, the amount of elemental sulfur is c, and c accounts for 1% to 10% of the mass of the lithium-rich lithium iron oxide, such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., preferably 2% to 8.5%, and further preferably 3% to 7%, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0028] Preferably, the amount a of the solid electrolyte, the amount b of the conductive carbon and the amount c of the elemental sulfur satisfy 1≤c / b≤5 and 3≤c / a≤10.

[0029] In the present application, if c / b>5 and / or c / a>10, the sulfur content is too high, the solid electrolyte and / or the conductive carbon content is too low, and an effective ion and electron conductive network cannot be formed in the elemental sulfur, affecting the lithium ion deintercalation. If c / b<1 and / or c / a<3, the sulfur content is too low, the solid electrolyte and / or the conductive carbon content is too high, which not only affects the effect of low-temperature coating, but also the adhesion and dispersibility provided by the molten elemental sulfur are insufficient. At the same time, the mixed coating layer formed cannot effectively improve the gas production problem. The solid electrolyte and / or the conductive carbon content are too high, which will also lead to a decrease in lithium replenishment capacity and increase costs.

[0030] It should also be noted that, relative to lithium-rich lithium iron oxide, the total amount of solid electrolyte, conductive carbon and elemental sulfur will also affect the thickness of the mixed coating layer. The thickness of the mixed coating layer should be at least 5nm to ensure uniform coating, and capacity attenuation caused by excessive coating should also be avoided.

[0031] As a preferred technical solution of the present invention, the temperature of the low-temperature heat treatment is 110-130°C, 110°C, 113°C, 115°C, 118°C, 120°C, 123°C, 125°C, 128°C or 130°C, etc., and the time is 1-3h, for example, 1h, 1.3h, 1.5h, 1.8h, 2h, 2.2h, 2.5h, 2.8h or 3h, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0032] In a second aspect, the present invention provides a lithium-rich lithium iron oxide lithium supplement, wherein the lithium-rich lithium iron oxide lithium supplement is obtained according to the synthesis method described in the first aspect.

[0033] In a third aspect, the present invention provides a battery, wherein the battery contains the lithium-rich lithium iron oxide lithium supplement agent described in the second aspect.

[0034] It should be noted that the lithium-rich lithium ferrate lithium supplement agent of the present invention is applicable to existing tableting and battery assembly processes without the need for additional process improvements.

[0035] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0036] The solid electrolyte, conductive carbon and elemental sulfur are mixed, subjected to low temperature heat treatment to form a composite mixture, and then mixed with lithium-rich ferrite and subjected to low temperature heat treatment to form a mixed coating layer to obtain a lithium-rich ferrite lithium supplement. The present invention adds sulfur to the mixed coating layer to absorb the surface oxygen released during the charging process of the lithium-rich ferrite, thereby reducing gas production; by adding solid electrolyte and conductive carbon, a conductive network of ions and electrons is formed in the sulfur-based mixed coating layer to avoid the Li+ caused by excessive sulfur coating. +At the same time, the elemental sulfur melted in the two low-temperature heat treatments can play a role in dispersion and bonding, achieving uniform dispersion of solid electrolyte and conductive carbon and effective coating of the composite mixture, and is conducive to improving the binding and compatibility. The mixed coating layer obtained by the mutual coordination of the three components can effectively improve the air stability of the lithium supplement. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a schematic diagram of the structure of the lithium-rich lithium ferrate lithium supplement obtained in Example 1. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0039] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.

[0040] Example 1

[0041] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement, the method comprising:

[0042] The lithium source anhydrous lithium hydroxide, the iron source nano-iron oxide and the additive zirconium oxide are solid-phase mixed, and the amount of the lithium source and the iron source is controlled according to the molar ratio of the lithium element in the lithium source to the iron element in the iron source of 5.2:1, and the amount of the additive accounts for 0.4% of the mass of the lithium-rich lithium ferrite theoretically generated by the lithium source and the iron source. The obtained solid phase mixture is pre-calcined at 470°C for 20 hours, and then sintered at 810°C for 7 hours to obtain lithium-rich lithium ferrite doped with zirconium element; the obtained lithium-rich lithium ferrite is crushed, and then the solid electrolyte LATP accounting for 0.7% of the mass of the lithium-rich lithium ferrite and the solid electrolyte LATP accounting for 1.5% of the mass of the lithium-rich lithium ferrite are firstly added. The conductive carbon SP (conductive carbon black) and the elemental sulfur accounting for 3% of the mass of the lithium-rich iron oxide are solid-phase mixed, and then low-temperature heat treatment is carried out at 120°C in a rotary kiln for 2 hours. After cooling, a composite mixture is formed, and then lithium-rich iron oxide is added for secondary solid-phase mixing. After the mixing is completed, the obtained solid-phase mixture is placed in a rotary kiln and then subjected to secondary low-temperature heat treatment at 120°C for 2 hours. The temperatures of the low-temperature heat treatment and the secondary low-temperature heat treatment can melt the elemental sulfur and bond it to the solid electrolyte and the conductive carbon, and together (i.e., the composite mixture) form a mixed coating layer on the outer surface of the lithium-rich iron oxide to obtain a lithium-rich iron oxide lithium supplement.

[0043] Figure 1It is a schematic structural diagram of the lithium-rich lithium iron oxide lithium supplement agent obtained in Example 1, in which the lithium-rich lithium iron oxide lithium supplement agent has a matrix of lithium-rich lithium iron oxide as the inner core, and a mixed coating layer is coated on its surface, wherein the mixed coating layer has a relatively high content of elemental sulfur as the matrix, and relatively low content of solid electrolyte and conductive carbon are uniformly dispersed in the elemental sulfur, the solid electrolyte and the conductive carbon form an ion conductive network and an electronic conductive network respectively, and together form a composite coating network in the elemental sulfur matrix to form a uniform mixed coating layer.

[0044] Example 2

[0045] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthesis method adjusts the amount of elemental sulfur from 3% to 0.5% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0046] Example 3

[0047] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthesis method adjusts the amount of elemental sulfur from 3% to 1% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0048] Example 4

[0049] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. In the synthesis method, the amount of elemental sulfur is adjusted from 3% to 5% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0050] Example 5

[0051] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthesis method adjusts the amount of elemental sulfur from 3% to 7% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0052] Example 6

[0053] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthesis method adjusts the amount of elemental sulfur from 3% to 10% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0054] Example 7

[0055] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthesis method adjusts the amount of elemental sulfur from 3% to 13% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0056] Example 8

[0057] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthesis method adjusts the amount of solid electrolyte from 0.7% to 0.1% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0058] Example 9

[0059] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthesis method adjusts the amount of solid electrolyte from 0.7% to 0.3% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0060] Example 10

[0061] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthesis method adjusts the amount of solid electrolyte from 0.7% to 1.4% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0062] Embodiment 11

[0063] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthesis method adjusts the amount of solid electrolyte from 0.7% to 2% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0064] Example 12

[0065] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement, wherein the amount of solid electrolyte is adjusted from 0.7% to 2.3% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0066] Embodiment 13

[0067] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthesis method adjusts the amount of conductive carbon from 1.5% to 0.5% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0068] Embodiment 14

[0069] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthesis method adjusts the amount of conductive carbon from 1.5% to 1% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0070] Embodiment 15

[0071] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthesis method adjusts the amount of conductive carbon from 1.5% to 2% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0072] Example 16

[0073] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthesis method adjusts the amount of conductive carbon from 1.5% to 2.5% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0074] Embodiment 17

[0075] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthesis method adjusts the amount of conductive carbon from 1.5% to 3% of the mass of the lithium-rich lithium iron oxide. Except for the above, other conditions are exactly the same as those in Example 1.

[0076] Embodiment 18

[0077] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. In the synthesis method, the temperature of the low-temperature heat treatment is adjusted from 120° C. to 100° C. Except for the above, other conditions are exactly the same as those in Example 1.

[0078] Embodiment 19

[0079] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. In the synthesis method, the temperature of the low-temperature heat treatment is adjusted from 120° C. to 110° C. Except for the above, other conditions are exactly the same as those in Example 1.

[0080] Embodiment 20

[0081] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. In the synthesis method, the temperature of the low-temperature heat treatment is adjusted from 120° C. to 130° C. Except for the above, other conditions are exactly the same as those in Example 1.

[0082] Embodiment 21

[0083] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. In the synthesis method, the temperature of the low-temperature heat treatment is adjusted from 120° C. to 160° C. Except for the above, other conditions are exactly the same as those in Example 1.

[0084] Embodiment 22

[0085] This embodiment provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthetic method does not use the additive. Except for the above, other conditions are exactly the same as those in Example 1.

[0086] Comparative Example 1

[0087] This comparative example provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthetic method does not use the elemental sulfur. Except for the above, other conditions are exactly the same as those in Example 1.

[0088] Comparative Example 2

[0089] This comparative example provides a method for synthesizing a lithium iron-rich lithium supplement. The synthesis method does not use the solid electrolyte. Except for the above, other conditions are exactly the same as those in Example 1.

[0090] Comparative Example 3

[0091] This comparative example provides a method for synthesizing a lithium-rich lithium iron oxide lithium supplement. The synthetic method does not use the conductive carbon. Except for the above, other conditions are exactly the same as those in Example 1.

[0092] Comparative Example 4

[0093] This comparative example provides a method for synthesizing a lithium iron-rich lithium supplement. The synthesis method does not use the solid electrolyte and the conductive carbon. Except for the above, other conditions are exactly the same as those in Example 1.

[0094] Characterization and Testing:

[0095] Ⅰ. The lithium-rich lithium iron oxide lithium supplement obtained in the examples and comparative examples was used as a positive electrode material to form a positive electrode sheet, which was then assembled and charged for a test.

[0096] Ⅱ. Record the mass of active material in the fully charged button electrode, inject electrolyte at a rate of 3.5g / Ah, seal it in an aluminum-plastic bag, and then store it at 60℃. Record the gas production during 7 days of storage.

[0097] Ⅲ. Conduct transmission electron microscopy test on the samples and record the thickness of the coating layer.

[0098] The above results are shown in Table 1.

[0099]

[0100] It can be seen from Table 1 that:

[0101] When the content and proportion of elemental sulfur, solid electrolyte and conductive carbon and the process conditions of the synthesis method are relatively suitable, the obtained lithium-rich lithium ferrite lithium supplement can take into account both capacity performance and air stability. The gas production when stored at 60°C for 7 days is <5mL / Ah, and can be further less than <3mL / Ah, and can be as low as <1.5mL / Ah.

[0102] Compared with Example 1, Example 2 has too low an amount of elemental sulfur, which affects the uniformity of the mixed coating layer formed by low-temperature coating, resulting in a reduced capacity of the obtained lithium supplement. At the same time, due to the low content of elemental sulfur in the mixed coating layer, its storage gas production is relatively high. In Example 7, due to the excessively high content of elemental sulfur, c / a and c / b are both large, resulting in the inability of the solid electrolyte and conductive carbon to form an effective ion and electron conductive network in the coating layer based on elemental sulfur, resulting in a low capacity. At the same time, although the total coating amount is high, the amount of Li released during charging is small. Therefore, the content of residual lithium in the electrode after charging is high, which is unstable during storage, but causes an increase in gas production.

[0103] Compared with Example 1, Example 8 has a too low solid electrolyte content, which affects the ionic conductivity, resulting in a decrease in the specific charge capacity, and further increases the gas production; Examples 11 and 12 have a low c / a value due to the excessively high solid electrolyte content. Since the solid electrolyte itself does not have electrochemical activity, the capacity is reduced, which in turn causes an increase in gas production.

[0104] Compared with Example 1, Example 13 has a low conductive carbon content, which affects the electronic conductivity, resulting in a decrease in the charge specific capacity, which in turn causes an increase in gas production; Example 17 has a high SP content, resulting in a low c / b value, and since the conductive carbon itself does not have electrochemical activity, it causes a decrease in capacity, which in turn causes an increase in gas production.

[0105] Compared with Example 1, Example 18 has very poor coating effect, extremely low capacity, and high gas production due to the low heat treatment temperature, and the elemental sulfur cannot be melted; Example 21 has too high a temperature for elemental sulfur treatment, which easily reacts with oxygen, resulting in the loss of elemental sulfur, affecting performance capacity and gas production. Therefore, for elemental sulfur with a melting point of 112.8°C under standard conditions, the temperature of the low-temperature heat treatment and the secondary low-temperature heat treatment in the present invention is preferably from 110 to 130°C, and more preferably from 118 to 126°C.

[0106] Since Example 22 is not doped, the ionic conductivity and air stability of the material are reduced to a certain extent, resulting in a decrease in capacity and an increase in gas production; since Comparative Example 1 is not coated with elemental sulfur, the gas production increases sharply, which is the highest among all the embodiments and comparative examples; since Comparative Examples 2, 3 and 4 do not add solid electrolytes and / or conductive carbon, the capacity decreases significantly, which also causes an increase in gas production.

[0107] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0108] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0109] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for synthesizing a lithium-rich lithium ferrate lithium supplement, characterized in that: The synthesis method comprises: A solid electrolyte, conductive carbon and elemental sulfur are mixed and subjected to a low-temperature heat treatment. The temperature of the low-temperature heat treatment causes the elemental sulfur to melt so as to bond the solid electrolyte and the conductive carbon to form a composite mixture based on elemental sulfur. The composite mixture is then mixed with lithium-rich lithium ferrite for a second time and subjected to a second low-temperature heat treatment so that the composite mixture forms a mixed coating layer on the surface of the lithium-rich lithium ferrite to obtain a lithium-rich lithium ferrite lithium supplement.

2. The method for synthesizing the lithium-rich lithium ferrate lithium supplement according to claim 1, characterized in that: The method for preparing the lithium-rich lithium iron oxide comprises: mixing a lithium source and an iron source in a solid phase, and then pre-sintering and sintering in sequence to obtain the lithium-rich lithium iron oxide.

3. The method for synthesizing the lithium-rich lithium ferrate lithium supplement according to claim 2, characterized in that: The lithium source includes at least one of lithium hydroxide monohydrate, anhydrous lithium hydroxide, lithium oxide, lithium carbonate or lithium nitrate; The iron source includes nano iron oxide, with a particle size of D 50 0.02~1μm; The amounts of the lithium source and the iron source are controlled according to the molar ratio of the lithium element in the lithium source to the iron element in the iron source of (5-5.6):

1.

4. The method for synthesizing the lithium-rich lithium ferrate lithium supplement according to claim 2, characterized in that: The method for preparing the lithium-rich lithium iron oxide further includes solid-phase mixing an additive with the lithium source and the iron source to dope the obtained lithium-rich lithium iron oxide; The additive includes at least one of zirconium oxide, aluminum oxide, tungsten oxide, titanium oxide or magnesium oxide; The amount of the additive used accounts for 0.1% to 1.2% of the mass of the lithium-rich lithium ferrite theoretically generated by the lithium source and the iron source.

5. The method for synthesizing the lithium-rich lithium ferrate lithium supplement according to claim 2, characterized in that: The pre-burning temperature is 400-550°C and the time is 5-40h; The sintering temperature is 700-850° C. and the sintering time is 5-15 hours.

6. The method for synthesizing the lithium-rich lithium ferrate lithium supplement according to claim 2, characterized in that: The amount of the solid electrolyte is a, and a accounts for 0.3% to 2% of the mass of the lithium-rich lithium ferrite; The amount of the conductive carbon is b, and b accounts for 1% to 2.5% of the mass of the lithium-rich lithium ferrite; The amount of elemental sulfur is c, and c accounts for 1% to 10% of the mass of the lithium-rich lithium ferrite.

7. The method for synthesizing the lithium-rich lithium ferrate lithium supplement according to claim 6, characterized in that: 1≤c / b≤5, 3≤c / a≤10; The thickness of the mixed coating layer is 5-20 nm.

8. The method for synthesizing the lithium-rich lithium ferrate lithium supplement according to claim 1 or 2, characterized in that: The temperature of the low temperature heat treatment is 110-130° C., and the time is 1-3 hours.

9. A lithium-rich lithium iron oxide lithium supplement, characterized in that: The lithium-rich lithium iron oxide lithium supplement Obtained according to the synthesis method according to any one of claims 1 to 8.

10. A battery, characterized in that: The battery contains the lithium-rich lithium ferrate supplement according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composite coated lithium-rich lithium ferrite positive electrode material and preparation method thereof

    CN117317177A

  • Positive electrode lithium supplementing material and preparation method thereof, positive electrode plate and lithium ion battery

    CN119361704A

  • Lithium supplement material and preparation method thereof

    CN119695116A

  • Preparation method for lithium-enriched solvent-philic lithium ion battery positive electrode material

    WO2024051186A1

  • Positive electrode material and preparation method therefor, positive electrode sheet, battery, and electric device

    WO2024234591A1

Cited By

  • Preparation method of lithium-supplementing positive electrode material, positive electrode plate and battery

    CN120914206A

  • Method for preparing lithium supplementing cathode material, positive electrode sheet and battery

    CN120914206B

  • Lithium supplement additive, preparation method thereof, positive plate and lithium ion battery

    CN121507169A

  • Lithium supplementing additive, preparation method thereof, positive electrode sheet and lithium ion battery

    CN121507169B